ANALYTICAL METHOD VALIDATION OF CYCLAMATE IN RED SYRUP IN NORTH BANJARMASIN USING UV-VIS SPECTROPHOTOMETER - Rahmawati; Andika; Rusmina Aulia Hasanah; Dhania Novitasari (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
Cyclamate is an artificial sweetener that is not allowed for public consumption, because it isspecifically permitted for diabetics and consumers with low-calorie diets. Syrup usuallyadded as a flavor enhancer (sweetener), color, and aroma. The purpose of adding artificialsweeteners to syrup is to reduce production costs because cyclamates have a highersweetness and lower price than sugar. The purpose of this study was to determine the contentand levels of cyclamate in syrup sold in various stalls and street sellers in the NorthBanjarmasin area, and to determine the data validation method with linearity, precision,accuracy, LOD, and LOQ. The results of the qualitative test showed that 4 of the 9 positivesamples contained cyclamate (samples A, C, E, and I). The results of the method validationparameter test for linearity at 20, 40, 60, 80, 100, and 120 ppm gave a value of thecorrelation coefficient (r ) of 0.9987 with an LOD value of 6.4307 ppm, LOQ of 21.4359ppm,d precision value of 0.74%, and an accuracy value of 89.5126%. The results of thequantitative tests were carried out on four samples, namely samples A, C, E, and I, withcyclamate levels of 12.9423, 31.9833, 23.4166, and 115.6469 mg/kg, respectively. Keywords: Cyclamate, Syrup, Precipitation, Validation Method, UV-Vis Spectrophotometry